Numerical modeling of the long-term poromechanical performance of a deep enhanced geothermal system in northern Québec - Saeed Vadiee; Biao Li; Jasmin Raymond; Mafalda M. Miranda (Rock Mechanics Bulletin, 2025)
This study numerically investigates the thermo-poromechanical effects in a Canadian geothermal reservoir caused by long-term fluid production and injection. Using finite element modeling, it explores pore pressure diffusion and thermal dynamics, incorporating both the geological structure of the rock mass and faults. The simulations utilize the IAPWS (International Association for the Properties of Water and Steam) equations to model fluid density and viscosity, ensuring realistic representations of heterogeneous pressure fields. The system replicates a doublet configuration within a faulted zone, featuring two hydraulically stimulated fractures. The primary aim is to assess the likelihood of fault reactivation under varying in-situ stress conditions over a 100-year geothermal operation. Results show that stress distribution is largely influenced by thermal stresses along the fluid circulation pathway, with fluid velocity and temperature gradients affecting reservoir stability. Minimal pore pressure changes highlight the dominant role of thermal stresses in controlling fault behavior. The analysis indicates no potential for fault reactivation, as slip tendency values remain below the critical threshold, even when accounting for reduced mechanical properties using the Hoek-Brown criterion. Thermal effects continue to influence the surrounding rock throughout the operational period, suggesting that the reservoir maintains mechanical stability conducive to sustained geothermal production and injection. These findings provide valuable insights into the long-term safety and behavior of geothermal reservoirs, offering important implications for future geothermal energy development and management strategies.